Integrated scheduling of port-centric supply chain: A special focus on the seaborne uncertainties. (20th July 2020) - Wang, Wenyuan; Xu, Xinglu; Peng, Yun; Zhou, Yong; Jiang, Ying
Abstract: The intricate structure of port-centric supply chain together with various uncertainties and participants existed make its scheduling issue complicated. To achieve an effective and cost-saving management, and meet the challenge of developing sustainable supply chain, this paper proposes a practical integrated scheduling model to minimize the over-all cost including production cost, storage cost, transportation cost, and final delivery penalty for a typical port-centric supply chain considering seaborne uncertainties. Specifically, not only a ship's uncertain arrival time, but also its uncertain departure time caused by variable draft requirements and tidal level are considered. Then, a multilevel coding genetic algorithm with reduced feasible region is developed to solve this bi-level decision-making problem. The results of a case study show that the integrated scheduling method proposed in this paper can save 13% of total cost compared to first-come/first-served scheduling and give a clear grasp on resource bottleneck in port-centric supply chain. Moreover, the green policy-"Take the Tide" permission-in the origin port can increase the practical draft depth and cut down the overall cost, but will bring more challenges in inventory management, especially for the destination port. Highlights: Integrated scheduling model development under various seaborne uncertainties. Proposed method verified a 13% reduction of total cost in the case study. A cost-effective scheduling under green maritime transportation development. "Take the Tide" scheduling is economical but brings harsh changes in port inventory. A supporting tool for system evaluation of the port-centric supply chain.